2021
DOI: 10.3389/fphar.2021.638950
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Macrophage Migration Inhibitory Factor in Acute Pancreatitis and Pancreatic Cancer

Abstract: Macrophage migration inhibitory factor (MIF) is a pleiotropic cytokine implicated in the pathogenesis of inflammation and cancer. It is produced by various cells and circulating MIF has been identified as a biomarker for a range of diseases. Extracellular MIF mainly binds to the cluster of differentiation 74 (CD74)/CD44 to activate downstream signaling pathways. These in turn activate immune responses, enhance inflammation and can promote cancer cell proliferation and invasion. Extracellular MIF also binds to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 135 publications
0
20
0
Order By: Relevance
“…Similary, Mif can regulate immune cell function through binding various receptors and its tautomerase activity (71,72). To examine the role of these factors in macrophage recruitment in our system, we treated Myc_OE tumor cells with a Cxcr2 inhibitor (AZD5069) or Mif inhibitor (ISO-1) in an in vitro transwell migration assay (52,70,72,73). Compared to vehicle controls, inhibition of Cxcr2 or Mif led to 2-10 fold decrease in macrophage migration (Fig.…”
Section: Myc Ehances Tam Recruitment and Metastasis Through Increased Expression Of Cxcl3 And Mifmentioning
confidence: 96%
See 1 more Smart Citation
“…Similary, Mif can regulate immune cell function through binding various receptors and its tautomerase activity (71,72). To examine the role of these factors in macrophage recruitment in our system, we treated Myc_OE tumor cells with a Cxcr2 inhibitor (AZD5069) or Mif inhibitor (ISO-1) in an in vitro transwell migration assay (52,70,72,73). Compared to vehicle controls, inhibition of Cxcr2 or Mif led to 2-10 fold decrease in macrophage migration (Fig.…”
Section: Myc Ehances Tam Recruitment and Metastasis Through Increased Expression Of Cxcl3 And Mifmentioning
confidence: 96%
“…The cognate receptor for Cxcl3 is Cxcr2, which has previously been reported to modulate myeloid cell recruitment in prostate cancer and PDAC (59,70). Similary, Mif can regulate immune cell function through binding various receptors and its tautomerase activity (71,72). To examine the role of these factors in macrophage recruitment in our system, we treated Myc_OE tumor cells with a Cxcr2 inhibitor (AZD5069) or Mif inhibitor (ISO-1) in an in vitro transwell migration assay (52,70,72,73).…”
Section: Myc Ehances Tam Recruitment and Metastasis Through Increased Expression Of Cxcl3 And Mifmentioning
confidence: 99%
“…Knockdown of ADM in pancreatic tumor-bearing mice significantly inhibited the recruitment of myelomonocytic cells and tumor angiogenesis ( Xu et al, 2016 ). Multiple studies have documented that elevated MIF expression was associated with increased tumor aggressiveness, reduced sensitivity to gemcitabine, and worse survival in PDAC patients ( Wen et al, 2021 ). Additionally, a previous study has identified DCBLD2 as a prognostic and diagnostic biomarker in PDAC ( Feng et al, 2021b ).…”
Section: Discussionmentioning
confidence: 99%
“…Another MIF inhibitor, ISO-1, was shown to inhibit pancreatic cancer cell invasion, migration and proliferation in vitro, as well as tumor growth in vivo in an immunodeficient murine model [ 106 ]. Given the importance of MIF in PDAC pathogenesis and pre-metastatic niche formation, inhibiting its effects on pre-metastatic niche formation in the neoadjuvant or perioperative setting may prove efficacious in reducing metastases [ 107 ].…”
Section: Clinical Translation: Diagnostic and Therapeutic Opportunitiesmentioning
confidence: 99%